Forms of development and land tenure as improvement tools of land use planning in Ukraine - Tretyak, A.; Kolganova, I. (Land Management, Cadastre and Land Monitoring, 2017)
Transformations which take place now in the the economy of Ukraine, and in particular in agriculture considerably exacerbated organizational and legal problems and organizational and territorial forms of local agricultural enterprises, protection of land ownership rights. Transformation of land relations violated the the traditional forms of organization of agricultural production, reduced the efficiency of capital investmenst in improvement of using and protection of land. Therefore, to improve the efficiency of agricultural land use in conditions of formation of market economy, general urgent of time is an in-depth analysis of the types and forms of land use which have found their consolidation at the legislative level. Land management is carried out throughout the country. It enveloped lands irrespective of unequivocal purpose, ownership and the character of using. But goals and objectives of land management, it’s content may be different. An important feature of land management are and it’s types. The current Land Code of Ukraineas the the Law of Ukraine "On Land Management" don’t contain legislative provisions on division of land management for certain types. Meanwhile, it should be noted, that normative and legal acts on land management of the Soviet period (Fundamentals of land legislation of the USSR and the United Republics 1968). Land codes 1978., 1990, 1992 there are two separate types of it - intereconomic (Modern terminology of A.M. Tretyak - territorial) and internaleconomic. Modern practice of the actions in the field of land management as evidenced by about the existence of another and a third type of land management – separational. Each of them is characterized by a specific purpose, carried out at different levels. It would therefore be appropriate, hat separate species of land management und their consolidation and in legislation level. Given that the process of implementation of land management for the object of land relations and cadastral accounting taken land plot, made sharing of agricultural land, where the owners of land shares allocated of land ownership, land use system, especially agricultural enterprises, significantly changed. All this has caused the emergence of a new type of territorial land management, which is aimed, especially in agriculture and environmental protection, on the organization of land use of legal entities and citizens, on the basis of combining of land plots, that being at different property rights. Therefore, should provide as a type of land management territorial planning of land ownership, land use, whose task is the formation of their territory, as is the case in developed foreign countries. Concerning intraeconomic land management, that under current conditions it’s explanation is somewhat different in new approaches to the regulation of land relations and the introduction of land use administration. Introduction of notion of land management forms will help to improve the structure and content of land management documents, and therefore the quality of tools of improvement of land-use planning at different hierarchical levels. Keywords: land use, land use types, forms of land management, land relations, land management documentation.